Price Indexes for PC Database Software and the Value of Code Compatibility - Dietmar Harhoff; Dietmar Moch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1996)
Changing product quality poses a challenge for the computation of price indexes, in particular in technologically advanced industries. We assess the differences between traditional and quality-corrected indexes by computing hedonic and matched-model price indexes for personal computer database software. Our database covers the price development in Germany from 1986 to 1994. Quality-adjusted software prices decline by 7.4 percent according to our hedonic index. Surprisingly, a matchedmodel index based on linking the prices of directly comparable program versions decreases even faster than the hedonic index (9.3 percent). This unusual result is apparently caused by the simultaneous selling of old and new versions of a given software product. The estimation results also confirm the importance of network effects. Code compatibility, i.e. the capability of executing programs written for the dominant database product, yields a significant price premium. The ability to read and write data in the dominant spreadsheet format (file compatibility) is also associated with higher prices, but the price differential is much smaller than in the case of code compatibility.
Keywords: 330; price indexes; hedonic methods; technical change; PC-Software; Preisindex; Hedonischer Preis; Produktqualität; Normung; Deutschland